Analysis of the Application of Concept Acquisition Learning Model in Improving Students' Mathematical Understanding - Abrar, Andi Ika Prasasti; Tilawah, Fathiyah Marsya; Saiyed, A. Rezki Amalia; Syaf, Hasrullah (AlphaMath : Journal of Mathematics Education, 2025)
This study investigates the implementation of the Concept Acquisition Learning Model (CALM) to enhance students’ conceptual understanding of mathematics at SMPIT Al-Biruni Mandiri Jipang in Makassar, South Sulawesi, Indonesia. Amidst growing concerns about low mathematics comprehension among middle school students, this research addresses an urgent need for innovative pedagogical approaches. Employing a descriptive qualitative design with a phenomenological method, data were gathered through classroom observations and in-depth interviews with a mathematics teacher using CALM in a seventh-grade class. The analysis, conducted through data reduction, presentation, and conclusion drawing, reveals that CALM fosters active student engagement and supports deeper comprehension of mathematical concepts. The findings underscore CALM’s potential as a novel and effective instructional strategy, capable of shifting passive learning patterns towards more meaningful cognitive involvement. While the model shows promise, its success is contingent on careful adaptation of teaching strategies and adequate time management. This study contributes to the growing discourse on mathematics education by positioning CALM as a viable alternative for improving conceptual learning outcomes in secondary education settings.